Extrusion of the distal ventriculoperitoneal shunt catheter through the umbilicus: a systematic literature review from 1973 to 2021 - Ghritlaharey, Rajendra K. (International Surgery Journal, 2021)
Trans-umbilical extrusion of the distal ventriculoperitoneal shunt catheter is a rare complication of the VPS insertion. The objectives of this review were to analyze various variables like the age, sex, indication for VPS insertion, clinical presentation, the operative therapy offered for the management, and outcome of the cases published/managed for the trans-umbilical extrusion of the distal VPS shunt catheter. In 1973, the maiden case of trans-umbilical extrusion of the distal VPS catheter was published. Literature/case reports were retrieved from 1973 to October 31, 2021. A total of n=24 (12 males, 12 females) cases were recruited for this systematic review. All of them were children below the age of 13-years. In four-fifths (n=19) of children, the initial VPS catheter was inserted during the first 6-months of life. The median age of children at the time of diagnosis of the above-described VPS complication was 7.5 (42.21 SD) months, and it ranged from 2 months to 13 years of age. The median interval from the initial VPS insertion/last VPS revision to the diagnosis of complication was 4 (24.77 SD) months, and it ranged from 3 weeks to 8 years. The main complaint was the extrusion of the distal VPS catheter through the umbilicus. Surgical procedures performed for the management were (a) removal of the entire VPS catheter n=15, (b) removal of distal/part of distal VPS catheter n=5, and (C) others n=2. For VPS catheter revision; delayed re-VPS insertion was performed in n=10, immediate revision of the distal VPS catheter in n=3, and others. Three (12.5%) children died during the postoperative and follow-up period. The distal VPS catheter extrusion through the umbilicus is a rare complication of VPS insertion, and it occurred exclusively in children. In 70% (n=17) of children, it was documented ≤6 months afterward of the VPS insertion. Delayed re-VPS catheter insertion was preferred for 40% of the children for VPS revision procedures.